2013
DOI: 10.1007/s13402-013-0127-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-microenvironment interactions: role of tumour stroma and proteins produced by cancer-associated fibroblasts in chemotherapy response

Abstract: Increasing evidence is emerging showing that tumour-stroma interactions may not only affect tumour progression and patient prognosis, but also the response to chemotherapy. The tumour stroma-derived biomarkers that appear to be most appropriate to determine the patient's response to chemotherapy vary by tumour origin and the availability of pre-treatment tissue. For patients scheduled for adjuvant chemotherapy, the most promising biomarker appears to be the PLAU: SERPINE complex, whereas for patients scheduled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 140 publications
1
38
0
1
Order By: Relevance
“…This appearance is consistent with what one would expect of a subtype in which stromal cells, as well as lymphocyte infiltration, dilute the tumor-intrinsic subtype signal. Also consistent with the notion of TP53-like tumors being partly defined by extrinsic factors, this class of tumors responds poorly to chemotherapy [2], a suggested feature of macrophage/ stroma-infiltrated tumors [7,8]. The MDA basal subtype is the most clearly defined and corresponds directly to the Lund basal/SCC-like subtype.…”
supporting
confidence: 73%
“…This appearance is consistent with what one would expect of a subtype in which stromal cells, as well as lymphocyte infiltration, dilute the tumor-intrinsic subtype signal. Also consistent with the notion of TP53-like tumors being partly defined by extrinsic factors, this class of tumors responds poorly to chemotherapy [2], a suggested feature of macrophage/ stroma-infiltrated tumors [7,8]. The MDA basal subtype is the most clearly defined and corresponds directly to the Lund basal/SCC-like subtype.…”
supporting
confidence: 73%
“…Recent work has uncovered the importance of both LEPs and MEPs in breast cancer development, thereby opening avenues to revisit the potential of this retinoid-based therapeutic approach. We hypothesize that, although the solid tumour environment is complex and heterogeneous [26], changes in pathological conditions accomplished through differentiation induction may affect patients with cancer, i.e., differentiated cells may become more susceptible to conventional therapies, leading to better therapeutic responses. Retinoic acid is the active metabolite of vitamin A, playing a key role in controlling the development, proliferation and differentiation of diverse cell types [27], including embryonic and adult cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it becomes increasingly clear that tumor-stroma interactions not only influence the development of the tumor and the prognosis of patients, but also the response to chemotherapy [60]. Efstathiou et al reported that preoperative treatment of metastatic prostate cancer with thalidomide induces a decrease in the microvasculature and transition to a less aggressive stromal-epithelial phenotype (e.g., a decrease in the expression of metalloproteinase in favor of E-cadherin) [61].…”
Section: Relations Between Surgery and The Tmv: Clinical And Research Sigmentioning
confidence: 99%